Study on coal permeability evolution considering adsorptive deformation characteristics of matrix - Gang WANG; Mingzhen WANG; Zhiyong XIAO; Xiaoxiang SUN; Wenwen JIA; Feng JIANG; Chengcheng ZHENG (Meitan kexue jishu)
Permeability is an essential parameter in CBM exploration and greenhouse gas storage. Accurate understanding of gas flow in coal seam can not only reasonably predict CBM production, but also improve the efficiency of CO2 geological storage. The general coal rock permeability prediction model is from the effective stress and gas adsorption point of view for the theoretical derivation of the model, but in practice, the complexity and uncertainty of the internal structure of the matrix of the coal rock, and adsorption related to the distribution of the mineral constituents of the phenomenon of inhomogeneous, which tends to ignore the matrix region of non-uniform adsorption deformation of the influence of this factor. Therefore, in this paper, the matrix region of coal and rock is divided into two regions with different adsorption capacity, and the permeability model of coal and rock is re-derived. The field data and laboratory data are used to compare and verify the proposed model, and the influence of non-uniform adsorption of matrix region on permeability evolution is analyzed by finite element software. The results show that: ① The proposed model has a high matching degree with field and laboratory experimental data, and the permeability prediction data under different boundary conditions have high reliability. ② The permeability of the non-adsorption expansion area of the matrix will be reduced by the squeezing effect of the adsorption expansion area, and the closer to the adsorption expansion deformation area, the stronger the squeezing effect, and the more obvious the reduction in permeability of the non-adsorption expansion area. ③ With the increase of the adsorption area of the matrix, the stress disturbance of the adjacent matrix region will be earlier, and the gas permeability will be lower when the compressed matrix region is in equilibrium. The improved permeability model can better understand the influence of regional matrix interaction in coal and rock on permeability, and has certain theoretical guiding significance for coalbed methane exploitation.